Studies Progression on the Function of Autophagy in Viral Infection - Liang, Weizheng; Liu, Huimin; He, Junli; Ai, Lisha; Meng, Qingxue; Zhang, Weiwen; Yu, Chengwei; Wang, Hao; Liu, Hui (Frontiers in Cell and Developmental Biology, 2021)
Autophagy is a conservative lysosomal catabolic pathway commonly seen in eukaryotic cells. It breaks down proteins and organelles by forming a two-layer membrane structure of autophagosomes and is involved in the circulation of substances and the maintenance of homeostasis. Autophagy can play a dual role in viral infection. Depending on the virus replication cycle, it can serve either as a pro-viral factor or, alternatively, as an antiviral defense element. Recent studies have suggested the complicated and multidirectional role of autophagy in the process of virus infection. On the one hand, autophagy can orchestrate immunity to curtail infection. On the other hand, some viruses have evolved ways to escape autophagy degradation whereby facilitating their own replication. In this review, we summarize recent progress of the interaction between autophagy and viral infection. Furthermore, we highlight the link between autophagy and SARS-CoV-2, which is expected to guide the development of effective antiviral treatments to combat infectious diseases.